Penyuluhan Dan Dan Pelatihan Pembuatan Sabun Cuci Piring Di Perumahan Griya Serpong Asri Cisauk Kota Tangerang Selatan - Supriyadi, Edi; Dewanti, Rully Nur; Sofyan, Soleh; Junaedi, Junaedi; Kurniasih, Nia (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
Improving social welfare can be done with various approaches, by empowering the community. Empowering PKK women in Griya Serpong Asri, Suradita, through training and assistance in washing soap production plate. This activity is carried out in order to improve human resources who is able to rely on his own strength. Specific objectives and targets This PKK ladies are interested and motivated to be achieved in this activityentrepreneurship, forming groups of PKK members who became independently independenteconomy by producing dishwashing soap, and realizing more PKKstronger, more productive, creative and responsive. To achieve this goal, teamcommunity service Industrial Engineering Study Program has provided counseling, training and assistance of PKK mothers in producing laundry soap plate. PKK ladies were given knowledge about entrepreneurs and business opportunities home based, as well as basic principles of production. PKK ladies were also given training on how to make dish soap, and product packaging marketing technique.